Turismo arqueológico em Sergipe: do espaço de contemplação à construção de cenários arqueológicos para práticas turísticas - Alves, Laura Almeida de Calasans (2019)
The thesis starts from the problem of the non-consolidation of the archeological tourism in Sergipe, under the justification of the absence of monumentality of the archaeological remains. The hypothesis, initially elaborated, supports the assumption that the lack of construction of touristic archeological scenarios, based on local specificities, is the cause of this non-consolidation. The general aim of the study is to analyze the practicability in the deve lopment of archaeological scenarios for touristic practices in Canindé de São Francisco and São Cristóvão, under the bias of tourism of experience, that can contribute to local development, considering the process of interpretive, participative and sustainable planning of the archaeological patrimony in Sergipe. The survey showed that the lack of monumentality is not an obstacle to local archaeotourism, as it proved that Sergipe, although not yet consolidated as a national tourism destination, is home to one of the most important archaeological research centers in the country, rich in material vestiges, pre-colonial and historical sites that witness the vast occupation of past societies in the present territory that we call Sergipe. The study proposed the methodology of construction of scenarios equally to its dimensions and variables, a qualitative study, bibliographical, exploratory and descriptive characterized, using the content analysis of Bardin, within the proposal of socio-enviro nmental knowhow, presenting a participative management model through the patrimonial interpretation. The choice of this methodology allowed archeology and tourism, starting from mutual dialogue, to construct dynamic scenarios, through the direct involvement of goods and services, interacting concomitantly with local identity and culture, diversifying the new practices of tourism, although little discussed in academic literature, makes it possible to open an interdisciplinary issue about the interpretation of heritage, democratization of knowledge under the bias of sustainable models. The obtained results validate the hypothesis and confirm that the studied destinations have feasibility to practice archaeological tourism, and own proportional monumentality for this practice. As a result of this study it is suggested to concretize the archaeological tourism in Sergipe, the implantation of an interpretative archaeological plan and itineraries subdivided in thematic tracks, products of this thesis, supported in the conservation, strengthening of the local identity, preservation of the patrimony and promotion of the touristic destination and income generation, anchored in the new way of planning tourism integrated to archeology at the service of the community.